THE INFLUENCE OF LEARNING ORGANIZATION ON WORK EFFECTIVENESS WITH KNOWLEDGE SHARING MEDIATION IN PROCUREMENT OF GOODS/SERVICES - Ichtiano, David Julian; Hadiyati, Ernani; Muawanah, Umi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the impact of Artificial Intelligence (AI) adoption on the performance of Islamic banks in Indonesia, with a focus on the moderating role of economic uncertainty. Using panel data from 12 Islamic commercial banks from 2021 to 2024, AI adoption is measured through a composite index evaluating the scope and depth of technology implementation across four dimensions: customer service, operations and compliance, credit and risk analysis, and strategic investment. The analysis employs a random effects regression model. The findings reveal a nuanced perspective AI adoption does not yet have a significant effect on Return on Assets (ROA). Similarly, economic uncertainty and its interaction with AI are found to be insignificant. These results indicate that AI integration in Indonesian Islamic banking remains preliminary and lacks strategic depth. The primary determinant of bank performance remains operational efficiency (OE). This study provides critical empirical evidence that AI investment does not automatically translate into profitability in this specific context. The findings enrich the discourse on fintech implementation in emerging markets and offer a foundation for developing more effective digital strategies for Islamic banking.